2019
DOI: 10.3390/ijerph16203894
|View full text |Cite
|
Sign up to set email alerts
|

Pain Intensity among Community-Dwelling African American Older Adults in an Economically Disadvantaged Area of Los Angeles: Social, Behavioral, and Health Determinants

Abstract: Background. Although social, behavioral, and health factors influence prevalence and intensity of pain, very few studies have investigated correlates of pain among economically disadvantaged older African American (AA) adults. Objective. This study explored social, behavioral, and health correlates of pain intensity among community-dwelling AA older adults in an economically disadvantaged area of Los Angeles. Methods. A cross-sectional study on 740 AA older adults (age ≥ 55 years) was conducted in South Los An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 86 publications
(194 reference statements)
0
11
0
2
Order By: Relevance
“…This community-based cross-sectional study surveyed a convenience sample (n = 740) of older African Americans residing in South Los Angeles [3,4,6,[28][29][30][31]. Also referred to as "South Los Angeles" Service Planning Area 6 of Los Angeles County, which serves the communities of Athens, Compton, Crenshaw, Florence, Hyde Park, Lynwood, Paramount, and Watts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This community-based cross-sectional study surveyed a convenience sample (n = 740) of older African Americans residing in South Los Angeles [3,4,6,[28][29][30][31]. Also referred to as "South Los Angeles" Service Planning Area 6 of Los Angeles County, which serves the communities of Athens, Compton, Crenshaw, Florence, Hyde Park, Lynwood, Paramount, and Watts.…”
Section: Methodsmentioning
confidence: 99%
“…This subset of older adults is faced with numerous health disparities, including lower rates of preventative health services and a greater delay in care. Individuals enrolled in any type of nursing facility, enrolled in any other research study, and who have observable intellectual impairments, were excluded from this study [3,4,6,[28][29][30][31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Podem ser resultantes de catástrofes mais geograficamente localizadas como tsunamis (Yabe et al, 2017). Sofrimento econômico também ocorre isoladamente em indivíduos que contraem dívidas superiores a capacidade de pagamento (Ochsmann et al, 2009), ou que não dispõe de recursos para realizar as despesas básicas (Evans et al, 2019). Esse impacto parece apresentar maior grau em países menos desenvolvidos, devido à grande desigualdade social e educacional da população.…”
Section: Introductionunclassified
“…Multiple studies have shown that African-American older adults with experience chronic and intense pain may be untreated or under-treated for their pain [ 4 , 5 , 6 ]. A review of current literature clearly shows a disparity in the management of pain among older African-American adults [ 7 ].…”
Section: Introductionmentioning
confidence: 99%